REGIONAL SOCIALIZATION OF INDUSTRIAL CLUSTERS (ON THE EXAMPLE OF THE YAMAL-NENETS AUTONOMOUS DISTRICT) - A. S. Kharyuchi (Модернизация, инновация, развитие, 2015)
The conceptual vision of the foundations of socialization clusters as formation of a decision new system's way of social problems for the autonomous region industry clusters on a principles public-private partnership between business and government.